Penambahan bagian buah jeruk siam dan sukrosa pada pembuatan minuman isotonik air kelapa - Nisrina Hasna Nabila; Maherawati Maherawati; Suko Priyono (AGROINTEK, 2024)
Isotonic drinks are one of the carbonated or non-carbonated soft drink products to improve fitness. Isotonic drinks can be made from natural ingredients such as coconut water. Isotonic drinks can also be added with fruit parts, namely orange pulp juice and orange peel juice. Additional ingredients added in isotonic drinks are sucrose, citric acid, NaCl, and sodium benzoate. Sucrose is added to meet the standards for sucrose content and to enhance the sweet taste. Citrus slices are added for flavor and nutrition. The purpose of this study was to determine the best formulation of isotonic coconut water drink with variations of citrus and sucrose parts. This study used a single factor Randomized Block Design (RBD), namely the addition of sucrose and slices of citrus fruits, with 3 replications. Parameters observed were pH, sodium, potassium, total dissolved solids, antioxidant activity, organoleptic and microbial counts. The data obtained were analyzed using ANOVA (5%), followed by DMRT (5%). The best treatment was tested using the effectiveness index test. The results showed that the addition of sucrose and citrus fruit parts had an effect on total soluble solids, antioxidant activity, taste and overall preference in organoleptic tests. The isotonic drink of coconut water meets SNI for pH, sodium and total dissolved solids. The results of the effectiveness index test showed that the isotonic drink of orange coconut water with the addition of 6% sucrose and fruit peel was the best isotonic drink